Information System Audit: A Case Study of Bank Syariah Indonesia - Wafa, Zaenal; Airawaty, Diana; As'ari, Hasim (Jurnal Multidisiplin Sahombu, 2025)
The increasingly advanced development of technology requires the business world to compete competitively, effectively, and efficiently. PT Bank Syariah Indonesia, Tbk, is one of the companies engaged in the banking sector that has placed technology in achieving its goals. The company uses the workflow integrated system engine (WISE) application to process home ownership financing applications. The author identifies problems or weaknesses in the WISE application related to its performance, security, reliability, and functionality. This study aims to describe data in the form of tables and graphs. To determine the maturity level criteria for the WISE application. This study uses a quantitative research type, namely research that produces findings that can be obtained using statistical methods. This study focuses on the maturity level of the WISE application using the COBIT 4.1 framework. The average maturity score of each subdomain is at level 3.5, and its maturity index is in the range of 3.51 to 4.5, namely 3.51 to 4.5 at maturity level 4 (four), namely, managed and measurable. Regarding the results of the information system control maturity level expected in this study, the author obtained a score of 4.8 with a maturity index of 4.51 - 5.00 or level 5 or Optimization. Accounting information systems have become widely used in various organizations or institutions, both private and government. Remember that banking data is very sensitive because it is related to financial data, which needs to be supported by a reliable data security system. The vulnerability of information systems can result in data hacking by irresponsible parties. This qualitative research examines and analyzes audits of technology or IT-based information systems in Indonesian BUMN, in this case, Bank Syariah Indonesia, which is based on Risk Management with the Control Objectives for Information and Related Technologies (COBIT) framework1,2,3. The COBIT framework has been trusted as a reliable framework for assessing an organization's IT governance. This research found that Bank BSI has managed risk well in its IT-based system.